Ecology, engineering, and management reconciling ecosystem rehabilitation and service reliability - Eeten, Michel van (Oxford University Press, 2002)
This book presents an introduction, overview and extension of ecosystem management and environmental restoration principles and applications. It develops a new framework and approach to improving the environment through extensive case studies and analysis of environmental rehabilitation initiatives in the San Francisco Bay-Delta, Florida Everglades, Columbia River Basin in the Pacific Northwest, and the Green Heart region of western Netherlands. The book's comparative and; integrative approach, with its grounding in ecology, engineering and management, will appeal to those working wherever population, resources and environment are in conflict.
Keywords: Ecosystem management.; Environmental policy.; elektronické knihy; electronic books